Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Perspectives on the economic and political history of the Ross Sea - Basberg, Bjørn L.; Lintott, Bryan (The Polar Journal, 2023)
The paper analyses the economic and political history of the Ross Sea, where exploration, science, commercial exploitation, politics and adventure became highly interlinked and interwoven. Expedition accounts and the extensive literature on Antarctic history and politics inform the contextual aspects. The archives of the Norwegian whaling company A/S Rosshavet, established in 1923, and the United States of America and New Zealand archival material from the 1950s are key sources. From the first whaling season onwards, the impact of Antarctic whaling, and later scientific bases, highlights and illustrates the tensions between Antarctic commerce, territorial claims and international politics.
Publisher: Routledge
Keywords: Sørishavet; historie; hvalfangst; politikk; økonomi

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Chr. Christensen and C. A. Larsen: A comparative analysis of two whaling entrepreneurs - Basberg, Bjørn L (International Journal of Maritime History, 2019)
Keywords: Antarktis; historie; hvalfangere; hvalfangst

Om C.A. Larsen og starten på pelagisk hvalfangst - Iversen, Ragnar (Skipet, 2017)
Keywords: Sørishavet; historie; hvalfangst

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Publisher: Norsk maritimt museum
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Publisher: Cambridge University Press
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Kvalfangst i Sørishavet - Knarvik, Olaf (Kjelda, 2009)
Keywords: Sørishavet; fotografi; hvalfangst

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

Fra Stangsgate til Sørishavet - Henningsen, Rune (Broen: aasgaardstrandiana, 2006)
Keywords: Sørishavet; historie; hvalfangst

Kvalfangst - Urdal, Sverre (Segn og soge: sogeblad for Ølen og Bjoa, 2006)
Keywords: Sørishavet; hvalfangst

Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Publisher: Norwegian School of Economics and Business Administration. Department of Economics Place: Bergen
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Helse på hvalfangst - Thoresen, Per (Vestfoldminne, 2002)
Publisher: Vestfoldmuseene
Keywords: Antarktis; arbeidsforhold; erindringer; helse; hvalfangere; hvalfangst; lege; medisin; pelagisk; sjøfolk; sjømenn

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst

Protecting whales by distorting uncertainty: non-precautionary mismanagement? - Schweder, Tore (Fisheries Research, 2001)
Precautionary management is based on science, and is incompatible with large fluctuations in the management regime. Whaling is managed by the International Whaling Commission, and has seen large fluctuations. It is argued that both the period of intense Antarctic whaling and the current period of protectionism have been unduly prolonged by scientists expanding out of proportion the uncertainty surrounding management issues. In the 1950s, uncertainty concerning fin whale stock status and trend was consistently distorted from one quarter, and in the 1990s a minority in the Scientific Committee blocked consensus over the revised management procedure that had been successfully developed by the Committee. In both cases, the political consequence of expanded uncertainty in the science was lack of action resulting in a continuation of business as usual. Extending a period of heavy exploitation longer than the resource can sustain is mismanagement. Extending a period of extreme protectionism when the resource is known to scientists to sustain valuable exploitation is also mismanagement even from a conservationist point of view. This might, in fact, erode the role of science in management and thus prepare the ground for subsequent overexploitation. Distorting uncertainty by injecting controversy or otherwise expanding uncertainty has contributed to excessive fluctuations in management regimes and consequently in stock abundance. Detrimental fluctuations might continue, since science is side tracked and management now is based on sentiments that might fade.
Keywords: Den internasjonale hvalfangstkommisjonen; Sørishavet; fiskeri; hvalfangst; marine økosystemer

Kvalfangsteventyret i Antarktis - Tokheim, Henrik (Vindetreet: sogeskrift for Vindafjord, 2001)
Keywords: Sørishavet; historie; hvalfangst

The Floating Factory: Dominant Designs and Technological Development of Twentieth-CenturyWhaling Factory Ships - Basberg, Bjørn L (The Northern Mariner/Le Marin du nord, 1998)
Keywords: Antarktis; historie; hvalfangere; hvalfangst; hvalkokeri

Kulturhistorisk forskning i Antarktis - Basberg, Bjørn Lorens (HIFO-nytt : medlemsblad for Norsk historikerforening, 1997)
Publisher: Historisk institutt, Universitetet i Oslo
Keywords: Antarktis; hvalfangst; kulturhistorie; kulturminner

Hvalfangstbase og kulturminne, Hektor Hvalfangststasjon : den sørligste av de norske landstasjonene i Antarktis - Rossnes, Gustav (Norsk sjøfartsmuseum. Årsberetning, 1997)
Publisher: Museet Place: Oslo
Keywords: Antarktis; Deceptionøya; Norge; fangststasjoner; hvalfangere; hvalfangst; hvalfangststasjoner

Hvalen – ressurs og politikk – Historisk overblikk - Fløistad, Brit (Vestfoldminne, 1995)
Publisher: Museumsforlaget
Keywords: Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Åpning av Foyn-seminaret 23.januar 1995 - Olsen, Jan Henry T (Vestfoldminne, 1995)
Publisher: Vestfoldmuseene
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Svend Foyn; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstkvotene; pelagisk

Hvalfangstlæge for 40 år siden - Husby, Jakob; Kolltveit, Bård (Norsk sjøfartsmuseum. Årsberetning, 1993)
Publisher: Museet Place: Oslo
Keywords: Anglo Norse ekspedisjonene; Sørishavet; erindringer; historie; hvalfangst; hvalkokerier; pelagisk

Hvalbåter over og under vann - Basberg, Bjørn L; Nævestad, Dag (Norsk sjøfartsmuseum Årsberetning, 1991)
Keywords: Sørishavet; historie; hvalfangst; skip

Hvalfangernes mat til hverdag og fest - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Sørishavet; ernæring; hvalfangst

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Pierce's kastebørse - et "Reodor Felgen" -patent med lang levetid - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Sørishavet; historie; hvalfangst; hvalolje; patenter; pelagisk; utstyr

Minnesmerket på Østre Halsen over antarktispioneren C.A. Larsen - Larsen, Hans-Kjell (Polarboken, 1988)
Keywords: Sørishavet; biografi; historie; hvalfangst

Kaptein C.A. Larsen: mannen som grunnla den moderne hvalfangsten i Sydishavet - Fagerli, Torkel (Polarboken, 1986)
Keywords: Sørishavet; biografi; historie; hvalfangst

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Ti nye år: Vestfold Historielag 60 år - Thoresen, Per (Vestfoldminne, 1984)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; hvalfangst; kulturhistorie; pelagisk

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Blåhvalen, kan de reddes? - Smelror, Morten (Naturen, 1981)
Keywords: Sørishavet; hvaler; hvalfangst

Hvalfangerne forteller. Innsammlig av hvalfangstens tradisjonsmateriale i Vestfold - Wexelsen, Einar; Devig, Thor N (Vestfoldminne, 1981)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangst; hvalfangstnæring; pelagisk

Smia på Fevang - Thoresen, Per (Vestfoldminne, 1976)
Publisher: Vestfoldmuseene
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangere; hvalfangst; pelagisk

Hvalfangstens historie - Tønnessen, Johan Nicolay; Solhaug, Trygve (Historisk tidsskrift, 1973)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Joh. N. Tønnessen: Den moderne hvalfangst historie. Opprinelse og utvikling. Bind 2-4. Utgitt av Norges hvalfangstforbund, Sandefjord 1967, 1969, 1970. - Solhaug, Trygve (Historisk tidsskrift, 1972)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Norwegian Antarctic whaling, 1905–68: an historical appraisal - Tønnessen, Johan Nicolay (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Norge; Sørishavet; historikk; hvalfangst; hvalfangstkvoten

Erobringen av Antarktis. Spredte glimt fra hvalfangstens historie - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1968)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk

Konsul Lars Christensen 6. april 1884—10. desember 1965 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1967)
Publisher: Routledge
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

International co-operation in Antarctic whale marking 1960 to 1965 - Brown, S G (Norsk hvalfangst-tidende, 1966)
Keywords: Sørishavet; hvaler; hvalfangst

Minnetale over konsul Lars Christensen. Holdt i fellesmøte den 4de februar 1966 - Holtedahl, Olaf (Det Norske Videnskaps-akademi i Oslo, 1966)
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

En epoke var over. I desember 1965 døde Lars Christensen - Tønnessen, Johan Nicolay (Thor-glimt, 1966)
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

Discovery II in the Antarctic - Tønnessen, Johan Nicolay (Norsk hvalfangst-tidende, 1965)
Keywords: Sørishavet; historie; hvalfangst

Folketro på hvalfangst - Eriksen, Erling (Vestfold-minne, 1964)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Internasjonalt samarbeide i antarktisk hvalmerking fra 1957 til 1960, og en oversikt over spredningen av merkede hval i Antarktis - Brown, S G (Norsk hvalfangst-tidende, 1962)
Keywords: Sørishavet; hvaler; hvalfangst

Litt om hvalfangsten i Antarktis og dens framtid (bygget på Norsk hvalfangst-tidende) (Polarboken, 1960)
Keywords: Sørishavet; hvalfangst

Gjenfundne hvalmerker i den antarktiske fangstsesong 1959/60 = Whale marks recovered in the Antarctic whaling season 1959/60 - Brown, S G (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Norsk hvalfangst: hovedtrekk i utviklingen - Eckstrøm, Kåre (Sosialøkonomen, 1960)
Keywords: Sørishavet; historie; hvalfangst

Hvalfangsten og Vestfold - Hasvoll, Bertold (Sosialøkonomen, 1960)
Keywords: Sørishavet; hvalfangst

Kvotefordeling og inspeksjonsordning norske krav i hvalfangstrpolitikken: nøytrale vitenskapsmenn undersøker fangstgrunnlaget - Jahn, Gunnar (Sosialøkonomen, 1960)
Keywords: Sørishavet; hvalfangst; politikk

Gjenfundne hvalmerker i sesongene 1955/56 og 1958/59 i Antarktis og i Syd-Afrika i 1958 og 1959 = Whale marks recovered in the Antarctic seasons 1955/56, 1958/59, and in South Africa 1958 and 1959 - Brown, S G (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Spermhvalens forekomst i Sydishavet og månens eventuelle innflytelse på forekomstene = Occurrence of the sperm whale in the Antarctic and the possible influence of the moon - Holm, John L; Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Et hvalfangerbrev - Larsen, Tryggen (Magasinet for alle, 1959)
Keywords: Sørishavet; hvalfangst

Hvalmerking utført av norske hvalbåter i Antarktis i sesongene 1956/57 og 1957/58 : whale marking carried out by Norwegian catchers in the Antarctic, seasons 1956/57 and 1957/58 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvalfangst; marin zoologi

Gjenfunne hvalmerker i den antarktiske sesong 1957/58 = Whale marks recovered during the Antarctic whaling season 1957/58 - Brown, S G (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

En lege på hvalfangst - Martens, Odd (Polarboken, 1958)
Keywords: Sørishavet; hvalfangst; medisin

Hvalfangsten i Antarktis 1956-57; en orientering (Polarboken, 1957)
Keywords: Sørishavet; hvalfangst

Gjenfunne hvalmerker i Antarktis i sesongen 1956/57 = Whale marks recovered during the Antarctic whaling season 1956/57 - Brown, S G (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Er det ønskelig og forsvarlig å utvide sesongen for fangst av knøl i Sydishavet? = Is it desirable and justified to extend the open season for humpback whaling in the Antarctic? - Jonsgård, Åge; Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; marinbiologi

Rapport om hvalmerking utført av norske hvalbåter i Antarktis i sesongen 1955/56 = Report on whale marking carried out by Norwegian catchers in the Antarctic season 1955/56 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

En underbeskattet knølhvalbestand? = An underfished humpback population? - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marinbiologi

Hvalfangsten i Antarktis sesongen 1955-56 (Polarboken, 1956)
Keywords: Sørishavet; hvalfangst

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ash, C E (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Foreløpige beregninger av den sydlige bestand av store bardehval = Preliminary estimates of the southern populations of the larger baleen whales - Mackintosh, N A; Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ottestad, Per (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Internasjonal regulering av hvalfangsten: et tilbakeblikk og en vurdering - Ruud, Johan T (Samtiden, 1956)
Keywords: Sørishavet; forvaltning; historie; hvalfangst; politikk

Vet vi noe om bestanden av finnhval i Sydishavet? = Do we know anything about the stocks of fin whales in the Antarctic? - Ruud, Johan T (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Hvalkokeriet i arbeid: en populær orientering - Sundt, H (Polarboken, 1956)
Keywords: Sørishavet; hvalfangst

Om størrelsen på den antarktiske finnhvalbestand sett i relasjon til fangstens størrelse = On the size of the Antarctic fin whale stock relative to the size of the catch - Symons, H W; Mackintosh, N A; Brown, S G; Salvesen, H K (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Hvalfangst og lægearbeid - Albretsen, C S R (Tidsskrift for den Norske Laegeforening, 1955)
Keywords: Sørishavet; hvalfangere; hvalfangst; medisin

Den internasjonale regulering av hvalfangsten - Eckstrøm, Kåre (Polarboken, 1955)
Keywords: Sørishavet; hvalfangst; jus

Hvalfangsten i Antarktis i sesongen 1954-55 - Østbye, Harald (Polarboken, 1955)
Keywords: Sørishavet; hvalfangst

Sør i Norge, sør i isen: sagaen om en hvalfangerslekt - Torkildsen, Torbjørn (Polarboken, 1955)
Keywords: Sørishavet; biografi; hvalfangst

Internasjonalt samarbeid i hvalmerking : "Enern"s tokt til Sydishavet i 1953 : the voyage of the "Enern" to the Antarctic 1953 = International co-operation in whale marking - Clarke, Robert; Ruud, Johan T (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Internasjonalt samarbeid i hvalmerking : Annen del av "Enern"s tokt til Sydishavet 1953 og forsøk med hvalmerker utført på flytende kokerier sesongen 1954 : The second period of the voyage of the "Enern" to the Antarctic 1953 and trials with whale marks conducted on board floating factories in the season 1954 = International co-operation in whale marking - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Fra Den internasjonale hvalfangstkommisjons 5. årsmøte i London iår - Lie, Just (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst; politikk

From The International Whaling Commission's fifth annual meeting in London this year - Lie, Just (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

Hvalfangstsesongen i Antarktik i 1952-53 - Østbye, Harald (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

The Antarctic whaling season 1952-53 - Østbye, Harald (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

Finnes det et fredningsfelt for bardehval i Antarktis? = Does there exist a sanctuary for baleen whales in the Antarctic? - Schubert, Kurt (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Whale catching in the Antarctic season 1951/52 - Østbye, Harald (Norsk polar-tidende, 1952)
Keywords: Sørishavet; hvalfangst

Modern whaling and its prospects - Ruud, Johan T (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; forvaltning; hvaler; hvalfangst

Nye hvalfangstekspedisjoner = New whaling expeditions (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

The International Whaling Commission møtes i Cape Town (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

Omkring konsesjonsordningen for den pelagiske hvalfangst = Concession arrangement for pelagic whaling - Knudtzon, Hans Thomas (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst; jus

Whale catching in the Antarctic season 1950/51 - Østbye, Harald (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

Det italienske hvalselskap og Howaldtswerke - Westphal, Adolf (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst; politikk

Norsk hvalfangstpolitikk i etterkrigsårene - Knudtzon, Hans Thomas (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst; politikk

Summary of preceding article about the Norwegian whaling policy after the war - Knudtzon, Hans Thomas (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst; politikk

Blod, svette og tårer - Orud, Hilmar (Magasinet for alle, 1950)
Keywords: Sørishavet; hvalfangst

The Antarctic whaling season 1949/50 - Østbye, Harald (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst

Kort oversikt over den norske pelagiske hvalfangst 1939-1949 - Bogen, Hans (Liv og virke ved polene : polarboken 1949, 1949)
Publisher: Norsk polarklubb Place: Oslo
Keywords: Sørishavet; historie; hvalfangst

Elektrisk hvaldreping - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk; teknologi

Hvalbåt forlist i Antarktik = Catching boat wrecked in the Antarctic (Norsk hvalfangst-tidende, 1947)
Keywords: Sørishavet; forlis; hvalfangst

Vestfold og hvalfangsten - Bogen, Hans (Årbok for Den norske turistforening, 1947)
Keywords: Sørishavet; historie; hvalfangst; økonomi

Historien om Antarktis (Norsk hvalfangst-tidende, 1945)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; litteratur; selfangst

Hvalfangerne drar sørpå igjen: 2.000-2.500 norske hvalfangere engasjert (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Da hvalfangerne lurte tyskerne i Sydishavet: en god skrøne - Andersen, Ottar (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Tyskernes sjørøveri i Sydishavet: hvalskytter Finn Bryde forteller - Arnesen, Odd (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Fra seksti grader nord til seksti grader syd - Bogen, Hans (Polar-årboken, 1945)
Keywords: Antarktis; hvalfangst

Norges livsrom - Hoel, Adolf (Det nye Norge, 1944)
Publisher: <s.n.> Place: Oslo
Keywords: Antarktis; hvalfangst; internasjonal politikk; polarområdene; økonomi

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

Hvalfangsten og fettindustrien: norsk hvalolje for 1320 millioner kroner i årene 1920-1939 - Bruun, Svend Foyn (Polar-årboken, 1940)
Keywords: Sørishavet; hvalfangst

[The Norwegian sector in the Antarctic region] (Norway, Norwegian Trade Review, 1939)
Keywords: Dronning Maud Land; hvalfangst; internasjonal politikk

De norske opdagelser i Sydishavet: fra C. A. Larsens tid til Christensens ekspedisjon 1937 - Aagaard, Bjarne (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; hvalfangst; oppdagelsesreiser

Charting the Antarctic - Christensen, Lars (The Polar times, 1939)
Publisher: American Polar Society
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Recent Reconnaissance Flights in the Antarctic - Christensen, Lars (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; hvalfangere; hvalfangst; luftfoto; oppdagelsesreiser

The Course of Antarctic Exploration between Longitudes 20° W. and 110° E. Notes on the map compiled to accompany the paper by Mr. Lars Christensen - Christensen, Lars (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Lars Christensen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Farve og form på hvalfeltet - Finne, Henrik (Polar-årboken, 1939)
Keywords: Sørishavet; hvalfangst; kunst

Det nye norske land i Antarktis - Isachsen, Fridtjov (Mellanfolkligt samarbete, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

The new Norwegian dependency in the Antarctic - Isachsen, Fridtjov (Le Nord : Revue internationale des pays du nord = International review of the northern countries, 1939)
Keywords: Dronning Maud Land; Norge; geografi; hvalfangst; internasjonal politikk; polarområdene

Japan vil overta hegemoniet i hvalfangsten! - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangst; politikk; økonomi

Sydhavssesongen 1938-39 - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangst

Minneord om kaptein Gustav Bruun Bull - Bogen, Hans (Polar-årboken, 1938)
Keywords: Antarktis; biografi; hvalfangst

Små notater om de "menige" hvalfangere fra 1905-1930 - Bogen, Hans (Polar-årboken, 1938)
Keywords: Sørishavet; hvalfangst

Charting the Antarctic - Christensen, Lars (American-Scandinavian Review, 1938)
Publisher: American-Scandinavian Foundation
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Hvalfangsten: et tilbakeblikk og en oversikt på grunnlag av norske patenter - Swensen, T (Teknisk ukeblad : Norges fremste på teknologi, 1938)
Keywords: Sørishavet; hvalfangst; patenter; pelagisk; teknologi

Hvalfangst-kunsten og nordmennene (Polar-årboken, 1937)
Keywords: Sørishavet; hvalfangst; politikk

Moderniseringen av vår hvalfangstflåte: et viktig ledd i en rasjonell utnyttelse av hvalen - Christensen, Chr. Fred. (Polar-årboken, 1937)
Keywords: Sørishavet; hvalfangst; logistikk

The Story of Whaling - Hjort, Johan (The Scientific Monthly, 1937)
Publisher: American Association for the Advancement of Science
Keywords: Sørishavet; historie; hvalfangst

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Blåhvalungen legger på sig 100 kg. i døgnet - Ruud, Johan T (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; blåhval; hvalfangst; paleontologi; pelagisk; zoologi

En arbeidsnatt ombord i et hvalkokeri - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangere; hvalfangst; pelagisk; sjøfolk

Elektrisk hvalskytning - Weber, Albert (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangst; pelagisk; teknologi

Er vi nordmenn uundværlige i hvalfangsten? (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Publisher: Aschehoug
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Omkring navngivningen i hvalfangstflåten - Bogen, Hans (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst; logistikk

Over 400 000 hval og 1500 millioner kroner i løpet av 30 år, men hvor lenge vil det vare nu? - Bogen, Hans (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Hvor tusener nordmenn henter sitt utkomme: daglig liv på fangstfeltet i Sydishavet - Romnæs, Nils (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Blåhval - Ruud, Johan T (Kvalitet, 1936)
Keywords: Sørishavet; hval; hvalfangst

Fangstsesongen i Sydhavet 1933-34 (Norsk hvalfangst-tidende, 1935)
Keywords: Sørishavet; hvalfangst

Hvalfangstens aristokrati - Bogen, Hans (Polar-årboken, 1935)
Keywords: Sørishavet; hvalfangst

Human Activities and the Study of Life in the Sea: An Essay on Methods of Research and Experiment - Hjort, Johan (Geographical Review, 1935)
Publisher: [American Geographical Society, Wiley]
Keywords: Sørishavet; historie; hvalfangst

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Til Sydishavet - Christensen, Lars (Polar-årboken, 1933)
Keywords: Sørishavet; ekspedisjoner; hvalfangst

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

Antarctic Whaling Season, 1931–32 (Polar Record, 1932)
Publisher: Cambridge University Press
Keywords: Norvegia ekspedisjoner; Sørishavet; hvalfangst

Blaahvalfangsten i Antarctic 1929/30 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

Finnhvalfangsten i Antarctic 1929/30 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

Hvalraadets skrifter (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst; litteratur

Sydhavet: norske selskapers fangst av de forskjellige hvalarter sæsongen 1930/31 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

A Brief History of Whaling - Hjort, Johan (Polar Record, 1932)
Publisher: Cambridge University Press
Keywords: Sørishavet; historie; hvalfangst

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Relation of the Work of the Mawson and Norwegian Antarctic Expeditions, 1930-1931 - Joerg, Wolfgang Louis Gottfried (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Fangst og forskning i Sydishavet (Norsk hvalfangst-tidende, 1931)
Keywords: Sørishavet; historie; hvalfangst; litteratur

Antarctic Research by the "Norvegia" Expeditions and Others: Discussion - Goodenough, William; Christensen, Lars; Kemp, Stanley; Wordie, James Mann; Mill, Hugh Robert (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Norvegia ekspedisjonen; ekspedisjoner; forsking; hvalfangst

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Fangstoversigt for Rosshavsfeltet sæsongen 1929-30 - Dingsør, Bernt (Norsk hvalfangst-tidende, 1930)
Keywords: Sørishavet; hvalfangst

The "Norvegia" Antarctic Expedition of 1929-1930 - Riiser-Larsen, Hjalmar (Geographical Review, 1930)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

Nitrates and Phosphates in the Southern Seas - Ruud, Johan T (ICES Journal of Marine Science, 1930)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hval; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

Hvalfangsten langs iskanten i Vest-Antarktis og ved Syd Shetland sæsongen 1928-29 (Norsk hvalfangst-tidende, 1929)
Keywords: Sørishavet; hvalfangst

Rosshavet (Norsk hvalfangst-tidende, 1929)
Keywords: Sørishavet; hvaler; hvalfangst

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Odd I.; Peter I. Øy; Sørishavet; ekspedisjonen; ekspedisjoner; historie; hval; hvalfangst

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Publisher: Routledge
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Hvalmaalinger i Rosshavet (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

"Southern Queen"s forlis (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; forlis; hvalfangst

Syd-Ørkney: sæsongen 1926/1927 (Norsk hvalfangst-tidende, 1927)
Keywords: Sørishavet; hvalfangst

Syd Shetland (Norsk hvalfangst-tidende, 1927)
Keywords: Sørishavet; hvaler; hvalfangst

H.J. Bull. Sydhavsekspeditionen 1893/1895 (Norsk hvalfangst-tidende, 1926)
Keywords: Sørishavet; ekspedisjoner; historie; hvaler; hvalfangst

Syd Shetland: sæsongen 1925/26 (Norsk hvalfangst-tidende, 1926)
Keywords: Sørishavet; hvalfangst

Rosshavet - Tofte, Eyvind (Norsk hvalfangst-tidende, 1926)
Keywords: Antarktis; Sørishavet; ekspedisjoner; hvalfangst

A/S "Rosshavet" (Norsk hvalfangst-tidende, 1925)
Keywords: Sørishavet; hvalfangst

Syd-Shetland: sæsongen 1924/1925 (Norsk hvalfangst-tidende, 1925)
Keywords: Sørishavet; hvalfangst

Hvalfangst i Rosshavet - Risting, Sigurd (Norsk hvalfangst-tidende, 1923)
Keywords: Sørishavet; ekspedisjoner; historie; hvaler; hvalfangst

Fangst i Sydhavet (Norsk hvalfangst-tidende, 1917)
Keywords: Antarktis; Sørishavet; ekspedisjoner; fangst; historie; hvalfangst; selfangst

The First Landing On The Antarctic Continent : being An Account of the Recent Voyage Of The Whaler "Antarctic" - Borchgrevink, Carsten Egeberg (The Century illustrated monthly magazine, 1896)
Publisher: The Century Co. Place: New York
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

A Voyage to the Antarctic Sea - Borchgrevink, Carsten Egeberg (Report of the Sixty-Fifth meeting of the British Association for the Advancement of Science helt at Ipswich in September 1895, 1895)
Publisher: John Murray Place: London
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The "Antarctic's" Voyage to the Antarctic - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1895)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the “Antarctic” to Victoria Land - Borchgrevink, Carsten Egeberg (Nature, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi